Efficient JPEG image steganography using pairwise conditional random field model - Pan, Yuanfeng; Ni, Jiangqun; Liu, Qingliang; Su, Wenkang; Huang, Jiwu (Signal processing, 2024)
Recent research shows that the security performance of JPEG image steganography can be improved by developing an accurate statistical model to characterize the correlations between Discrete Cosine Transform (DCT) coefficients. In this paper, a novel JPEG steganographic scheme called J-CRF is proposed to characterize the correlations between DCT coefficients using a pairwise Conditional Random Field (CRF) model, in which the correlated DCT coefficient pairs are modeled as bivariate Gaussian random variables. Under the framework of pairwise CRF, the proposed scheme formulates the problem of minimizing the statistical detectability within the Gaussian image model as the minimization of the sum of a series of unary and pairwise potentials, both of which are utilized to measure the local detectability of embedding messages in the DCT coefficient pairs. All the potentials associated with statistical detectability are formalized as the KL divergence between the statistical distributions of the cover and the stego. Experimental results demonstrate that the proposed J-CRF can outperform other SOTA JPEG steganographic schemes, e.g., J-UNIWARD, J-MiPOD, and JEC-RL, in resisting the detection of various advanced steganalyzers. In addition, the performance of J-CRF could be further boosted by reformulating it as the weighted sum of unary and pairwise potentials, called J-CRFW. •Propose a novel JPEG steganographic scheme J-CRF using Conditional Random Field (CRF).•Characterize the correlations between DCT coefficients using pairwise CRF.•Cast the task of JPEG steganography as minimizing the detectability with CRF.•Improve J-CRF by reformulating the sum of potentials in a weighted manner.•Demonstrate superior security performance over other SOTA schemes.